The Online Shopping Experience During the Pandemic and After—A Turning Point for Sustainable Fashion Business Management? - Suzana Demyen (Journal of Theoretical and Applied Electronic Commerce Research)
The present paper studies the changes that occurred in the clothing trade during the COVID-19 pandemic and the influences exerted on business management. The pandemic sped up digitalization, pushing companies to quickly adapt to new economic conditions and marking a turning point for online commerce. In the fashion sector, where consumer behavior has shifted rapidly and digital technologies have transformed the business landscape, it is essential to examine these changes and their long-term impact. The research methodology involved an online questionnaire-based survey, targeting 153 respondents from various age groups. Descriptive statistics were used, such as the analysis of variation indicators, to explore patterns in the data and provide a clearer understanding of the phenomena studied. Additionally, a series of statistical tests were applied to validate the research questions. The aim was not to predict future behavior but to explain current trends and shifts, particularly the acceleration of digitalization during the pandemic. The findings highlight changes in customer behavior, the need for investments in technology and innovation, and the importance of adaptability, especially in marketing. There is a statistically significant relationship between income levels and spending on clothing, with higher incomes leading to increased expenditure. The pandemic amplified the role of online channels, particularly among higher-income groups. Promotional campaigns significantly impact purchase decisions, especially for lower-income consumers, serving as both purchase drivers and tools for customer retention. The shift toward online shopping, accelerated by the pandemic, highlights substantial growth potential for e-commerce in the fashion sector. Consumers favor platforms offering convenience, product diversity, and personalized experiences. A moderate interest in sustainable fashion was observed, with preferences leaning toward affordable and durable materials, underscoring the need for transparent and eco-friendly business practices.